Efficient and secure authentication scheme with user anonymity based on cloud computing in 6G - Ying, Songpeng; Jiang, Zhilin (Frontiers in Physics, 2025)
With the rapid development of 6G and the widespread adoption of cloud computing technologies, security issues in distributed cloud computing systems have become increasingly critical. Ensuring user anonymity, legitimate device access, communication security, and efficient authentication has emerged as an urgent challenge. To address these issues, this paper proposes an anonymous, secure, and efficient authentication scheme for 6G cloud computing. The scheme supports both user authentication and device access authentication by integrating Chebyshev chaotic mapping with a multi-factor authentication mechanism. It ensures secure verification of user identities and access devices and protects subsequent session keys. Furthermore, a Physical Unclonable Function (PUF) is deployed on the device side to leverage unique hardware features, providing strong identity recognition and resistance to physical attacks while improving system authentication efficiency. Performance evaluations demonstrate that the proposed scheme reduces computational overhead by an average of 30.45% and communication overhead by an average of 16.32% compared with the baseline scheme. These results confirm that the proposed scheme significantly enhances communication security between authorized users, legitimate devices, and cloud servers in 6G cloud computing environments. By combining chaotic mapping, multi-factor authentication, and PUF-based verification, the scheme achieves robust security, lightweight computation, and strong scalability suitable for next-generation distributed cloud systems.